The Influence of Entrepreneurship Education and Family Environment on Entrepreneurial Interest Through Self-Efficacy (Study on XI Class Students in The Concentration of Digital Business Expertise SMK In Kediri City) - Fitri, Febriana; Pratikno, Heri; Wardhana, Ludi Wishnu (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to examine the effect of entrepreneurship education and family environment on entrepreneurial interest through self-efficacy. By using this sampling technique, sampling can ensure a fair opportunity for each category in the population, especially class XI students majoring in Digital Business at SMK Kediri City. This means that the higher the Entrepreneurship Education received by students, the higher the level of influence on student self-efficacy. This means that the higher the family environment that students have, the higher the level of influence on student self-efficacy. This means that the higher the self-efficacy of students, the higher the level of influence on students` entrepreneurial interest. Entrepreneurship education has a direct effect on entrepreneurial interest. This means that the higher the entrepreneurship education received by students, the higher the level of influence on student entrepreneurship interest. Family environment has a direct effect on entrepreneurial interest. This means that the higher the family environment that students have the higher the level of influence on student entrepreneurship interest.